Wireless microelectrode arrays for selective and chronically stable peripheral nerve stimulation for hindlimb movement. (14th October 2021) - Frederick, Rebecca A; Troyk, Philip R; Cogan, Stuart F
Abstract: Objective . Maximizing the stability of implanted neural interfaces will be critical to developing effective treatments for neurological and neuromuscular disorders. Our research aims to develop a stable neural interface using wireless communication and intrafascicular microelectrodes to provide highly selective stimulation of neural tissue. Approach . We implanted a wireless floating microelectrode array into the left sciatic nerve of six rats. Over a 38 week implantation period, we recorded stimulation thresholds and movements evoked at each implanted electrode. We also tracked each animal's response to sensory stimuli and performance on two different walking tasks. Main results . Presence of the microelectrode array inside the sciatic nerve did not cause any obvious motor or sensory deficits in the hindlimb. Visible movement in the hindlimb was evoked by stimulating the sciatic nerve with currents as low as 4.1 µ A. Thresholds for most of the 96 electrodes we implanted were below 20 µ A, and predictable recruitment of plantar flexion and dorsiflexion was achieved by stimulating rat sciatic nerve with the intrafascicular microelectrode array. Further, motor recruitment patterns for each electrode did not change significantly throughout the study. Significance . Incorporating wireless communication and a low-profile neural interface facilitated highly stable motor recruitment thresholds and fine motor control in the hindlimb throughout an extensive 9.5 month assessment in rodent peripheral nerve. Results of this study indicate that use of the wireless device tested here could be extended to other applications requiring selective neural stimulation and chronic implantation.